Phosphorus species and chemical composition of water hyacinth biochars produced at different pyrolysis temperature. (June 2021) - Bottezini, Luana; Dick, Deborah Pinheiro; Wisniewski, Alberto; Knicker, Heike; Carregosa, Ingred Suellen Carvalho
Abstract: Soil application of biochar (BC) manufactured from nutrient-rich biomasses may be an effective strategy to reduce chemical fertilizer use. Chemical and molecular composition and P species of water hyacinth BCs produced at 400 (BC400), 500 (BC500), and 600 °C (BC600) were assessed by elemental, chemical and spectroscopic (FTIR, 13 C and 31 P NMR) analysis. From BC400 to BC600, the contribution of O/N-alkyl C groups decreased from 15.2% to 1.7%, and that of aryl C increased (52% to 79%), thus confirming aromaticity increase. The total P content was around 7.5 g kg −1 and did not vary significantly within the BCs, whereas extractable P decreased with temperature (60 to 10 mg P kg −1 ). The dominant P species in the NaOH-EDTA extracts was orthophosphate. Our results suggest that, among the studied samples, BC400 poses as the most promising soil P-supplier, as indicated by its lower aromaticity degree and greater available P proportion. Graphical abstract: Unlabelled Image Highlights: Water hyacinth biochars were characterized by 13 C and 31 P NMR spectroscopy. Extractable P forms from water hyacinth biochars are mainly orthophosphate. Biochar produced at 400 °C contains 60 mg kg −1 of extractable P, 0.83% of total P. Aromaticity increased from 52 to 79% with pyrolysis temperature. Biochar produced at 400 °C is the most promising P-supplier.